Peak Systolic Blood Pressure During the Exercise Test: Reference Values by Sex and Age and Association With Mortality. Issue 6 (19th April 2021) - Assaf, Yazan; Barout, Ahmad; Alhamid, Ahmad; Al-Mouakeh, Ahmad; Barillas-Lara, Maria Irene; Fortin-Gamero, Sonia; Bonikowske, Amanda R.; Pepine, Carl J.; Allison, Thomas G.
Abstract : Supplemental Digital Content is available in the text. Abstract : We sought to update norms for peak systolic blood pressure (SBP) on the graded exercise test and examine its prognostic value in patients without baseline cardiovascular disease. Mayo graded exercise test data (1993–2010) were reviewed for nonimaging tests using Bruce protocol, selecting Minnesota residents 30 to 79 years without baseline cardiovascular disease. We formed a pure cohort of patients without factors significantly affecting peak SBP to determine peak SBP percentile norms by age and sex. Then we divided the full cohort of patients into 5 groups based on peak SBP percentiles: low (<10th), borderline low (10th–25th), referent (25th–75th), borderline high (75th–90th), and high (>90th). The relationship between peak SBP and mortality was tested using Cox regression adjusting for age, sex, and comorbidities affecting peak SBP or mortality. We identified 20 760 eligible patients with 7313 females (35%) and mean age 51.5±10.7 years. Our pure cohort included 7810 patients. Over 12.5±5.0 years follow-up, there were 1582 deaths, including 541 cardiovascular deaths. In the fully adjusted model, low-peak SBP was associated with increased total mortality (heart rate, 1.41 [1.19–1.66], P <0.0001) and cardiovascular mortality (heart rate, 1.54 [1.16–2.03], P =0.001), while borderline low-peak SBP was associated with increased cardiovascular mortality only (heart rate, 1.36 [1.02–1.81], P =0.027). High peak SBP was associated with increased total mortality only in the age-sex adjusted model (heart rate, 1.18 [1.02–1.36], P =0.026), not after full adjustment. We conclude that low exercise peak SBP is an independent predictor of higher total and cardiovascular mortality.